Norma Kesusilaan Sebagai Batasan Penemuan Hukum Progresif Perkara Kesusilaan Di Bangkalan Madura - Christianto, Hwian (Jurnal Hukum & Pembangunan, 2016)
Society definitely have different conception to the norms especially Bangkalan citizen, Madura. Once social case happen, judge confronted to decide according to decency norms. The Bangkalan State Court have arranged decency norm as main basic to judge social case. The decision is accepted as a law product which appoint to justice. This thought is in line with progressive law-founding which underline the essence of society values conception as an exist law. The decision of Bangkalan State Court have kept the social that highly suspended by people in Bangkalan Madura